Children’s and parents’/caregivers’ satisfaction with care at the children’s and adolescents psychiatric ward at Landspítali, the National University Hospital of Iceland - Birkir Bjarnason 1996- (2020)
When a child discharges from the children’s and adolescents psychiatric ward at Landspítali, the parents/caregivers answer a satisfaction survey regarding their experience of the care. In this study, children between the age of 12 to18 years old discharging from the psychiatric ward over the research period March 1st to May 15th, 2020, as well as their parents/caregivers were invited to participate. Both the parents/caregivers and the children filled out a satisfaction survey. The number of participants were 14, seven children and seven parents/caregivers. The data from both groups were compared. The results showed that no significant difference was between groups on the overall satisfaction with care. The children’s mean score was M = 7.33 (SD = 3.33) and the parents’/caregivers’ mean score was M = 8.71 (SD = 1.25). The children were less satisfied with all specific components regarding the care, although the difference was not significant. Age and diagnosis of depression and ADHD did not affect satisfaction significantly. The results do not fully correspond with other researches findings. The main limitation of the study was limited number of participants, partitialy due to COVID-19. Keywords: patient satisfaction, satisfaction survey, children’s and adolescent psychiatric ward, discrepancy Þegar barn útskrifast af legudeild barna og unglinga geðdeild Landsspítala (BUGL), svara aðeins foreldrar/forráðamenn þjónustukönnun varðandi reynslu sína af þjónustu deildarinnar. Í þessari rannsókn var öllum börnum á aldrinum 12 til 18 ára sem útskrifuðust af legudeild BUGL á tímabilinu 1. mars til 15. maí 2020, ásamt foreldrum/forráðamönnum, boðin þátttaka þar sem þjónustukönnun var lögð fyrir bæði foreldra/forráðamenn og barnið sem var að útskrifast. Þátttakendur voru 14 talsins, sjö börn og sjö foreldrar/forráðamenn. Svörin úr könnununum voru borin saman til að meta hvort munur væri á milli upplifunar hópanna á þjónustu deildarinnar. Niðurstöður rannsóknarinnar voru að ekki var marktækur munur milli hópanna á heildar ...